Nutrition Advocacy Through Strengthening Local Food in Pregnant Women in Stunting Prevention - Huriah, Titih; Maghpira, Dea Ainun (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Introduction: The prevalence of stunting under five in Indonesia is included in the country with the third highest prevalence in the Southeast Asia region or the South-East Asia Regional (SEAR). The average prevalence of stunting under five in Indonesia in 2005-2017 was 36.4%. One of the causes of stunting in toddlers is inadequate nutritional intake during pregnancy. One of the interventions that can be done is to provide nutrition advocacy related to local food for pregnant women. Purpose: The purpose of this case study was conducted to describe the nutritional status of pregnant women. Method: The method used is a case report. Overview of cases of G5P4A0 pregnant women. Currently the client is 20 weeks pregnant G5P4A0 5th pregnancy. The client has a history of the first pregnancy giving birth normally, the second pregnancy the client gave birth by SC because the womb had exceeded the HPL and was accelerated because there was no development for childbirth, the third pregnancy gave birth by SC because the distance between the first and second SC was only 23 months, the fourth pregnancy was done by SC because he has a history of SC 2 times, and the client is currently pregnant at high risk because he has a history of SC 3 times. The client had a history of giving birth to her first child with a baby weighing 1.8 kg and died after 3 hours of birth due to congenital abnormalities. At 20 weeks' gestation, the client's weight was 69 kg, TB was 154 cm and the weight before pregnancy was 65 kg. During this pregnancy the client does not do any diet or food restrictions, the client eats 2-3 times/day. The food that is often consumed by the family is side dishes and vegetables. Clients often consume fast food. The action taken is advocating local food nutrition for pregnant women. Results: Before the intervention was carried out the client said that he did not know about stunting prevention with local food. The results of the implementation given to the client were in the form of nutrition advocacy in the form of strengthening local food for pregnant women. The results obtained by the client were that they enthusiastically listened when they were given education and the client said that they now know and understand what local food is good for pregnant women. Education conducted for clients using audio-visual in the form of video and poster media aims to provide an understanding of the material so that it can increase the client's knowledge about the nutrition of pregnant women and can change the client's behavior in maintaining her pregnancy.